The art of the gunmaker - Hayward, J. F. (John Forrest), 1916-1983. (London : Barrie and Rockliff, 1962)
Set covers the whole range of craftsmen (barrel-smiths, lock-smiths, iron-chisellers, goldsmiths, enamellers, engravers, stockers, carvers, inlayers, gilders, and damasceners) along with the history of European and American firearms from 1500 to 1830.
v. 1. 1500-1660 -- v. 2. Europe and America, 1660-1830.
Includes bibliographical references and index.
Keywords: Gunsmithing; Firearms; Firearms; gunsmithing; Firearms; Gunsmithing; Firearms